An assessment of self-help water supply in Akure, Nigeria. (April 2018) - Fakere, Alexander Adeyemi; Folorunso, Clement Oluwole; Omole, Felix Kayode; Ayoola, Hezekiah Adedayo; Arayela, Olatunde
Abstract: Water is essential for human survival, and access to potable public water supply is crucial for household health. The prevalence of self-help water supply in Akure means that residents seek for water from untreated and unsafe sources. This paper argues that the absence of water supply from public water-supply infrastructure in the city is undesirable. We draw on information provided by focus groups representing five communities in the city. The findings revealed a wide array of self-help provision of water supply in the study area. We recommend the revivification of the dilapidated water-supply infrastructure in the study area. Highlights: The public water supply in Akure is dilapidated. Alternative sources of water supply are hand-dug well, boreholes, and so on. Water from these untreated sources is unsuitable for consumption. Competition amongst operators and adequate regulation could help resuscitate the failed public water mains.